The DNA damage-inducible gene DIN1 of Saccharomyces cerevisiae encodes a regulatory subunit of ribonucleotide reductase and is identical to RNR3. - Yagle, K (1990)
The sequence of the DIN1 gene of Saccharomyces cerevisiae is identical to RNR3, a gene encoding a DNA damage-inducible regulatory subunit of ribonucleotide reductase. Two sequence elements located upstream of DIN1 (RNR3) are homologous to putative DNA damage regulatory elements in the promoter of the reductase catalytic subunit gene, RNR2. The transcript start sites for DIN1(RNR3) have been localized, and induction by different agents has been compared with other DNA damage-regulated genes.